Hollandite-type β-FeOOH(Cl) as a new cathode material for chloride ion batteries. Issue 82 (17th September 2020) - Zhao, Guoqing; Wan, Gengping; Tang, Yulin; Xu, Xuefei; Zhou, Xuechun; Zhou, Maofan; Deng, Zhen; Lin, Shiwei; Wang, Guizhen
Abstract : β-FeOOH is utilized as a new cathode material for rechargeable chloride ion batteries for the first time. Abstract : β-FeOOH is utilized as a new cathode material for rechargeable chloride ion batteries for the first time. β-FeOOH has superior rate capabilities and a high reversible capacity of 122 mA h g −1 after 100 cycles. This work opens up new possibilities for the development of anion batteries.